Selection of optimal variants of surgical treatment of open arterial duct - Yu. V. Panichkin; I. O. Ditkovsky; E. V. Beshlyagha; A. Yu. Gavrilyshyn; Yu. L. Konopleva (Ukrainian Journal of Cardiovascular Surgery, 2018)
The purpose of the work.The purpose of this work is to compare surgical and endovascular methods of treatment of Patent Ductus Arteriosus (PDA) in order to determine the optimal method of correction.Materials and methods. The study included 1113 patients who performed a surgical or transcatheter correction of the defect in the interval from 2008 to 2017 on the basis of the GI ICVS named by. М. M. Amosоav NAMS of Ukraine. Surgical operations was performed in 452 patients (40.6%), and transcatheter correction was performed in 661 (59.4%) patients. The choice of the method of correction depended on the age and weight of the patient, the form of the PDA and the presence of concomitant complications.Results and discussion. Depending on the correction method, the optimal variants of the surgical treatment of the PDA are revealed. Significant differences in the effectiveness between surgical and transcatheter techniques were not detected, however, the number of perioperative complications showed a lower risk of transcatheter technique (1.2% vs. 10.5%), and a decrease in hospital stay (8–10 days for surgical correction up to 3–4 days with transcatheter method).Conclusions. The transcatheter technique for treating PDA is more secure than surgery, has less complications and is better tolerated by patients. However, despite the apparent advantages of the endovascular method, due to the high cost of devices for the PDA occlusion, further search for ways to improve and reduce the cost of transcatheter treatment for defects is necessary.